Benign Paroxysmal Positional Vertigo in Irradiated Nasopharyngeal Carcinoma Survivors. (24th October 2013) - Feng, Shaoyan; Fan, Yunping; Guo, Liqing; Liang, Zibin; Mi, Jiaoping
Abstract : Purpose . It has been assumed that postirradiated nasopharyngeal carcinoma (NPC) patients are prone to benign paroxysmal positional vertigo (BPPV). The purpose of this study was to better understand this clinical entity. Materials and Methods . From September 2003 to June 2011, we conducted a retrospective study of 11 irradiated NPC patients with BPPV in our institute. During the same period, 11 irradiated NPC patients without BPPV were randomly selected and enrolled as the control group. All medical records of these patients were evaluated. Results . The risk of BPPV rises significantly when the patient undergoes radiotherapy (RT) twice and the threshold radiation dose is >120 Gy (P = 0.027 ). The occurrence of postirradiated BPPV was significantly related to incidences of otitis media and sensorineural hearing loss (SNHL) (P = 0.011 and 0.009, resp.). All the patients responded well to repositioning maneuvers. Conclusion . A second course of RT, postirradiated otitis media, or SNHL is associated with the potential risk of radiation-induced BPPV. Repositioning maneuvers were safe and effective for relief of this disease.